2019
DOI: 10.1097/ico.0000000000002129
|View full text |Cite
|
Sign up to set email alerts
|

Correlation Between Corneal Biomechanical Indices and the Severity of Keratoconus

Abstract: Purpose: To investigate the correlations between the biomechanical indices determined in Scheimpflug-based corneal biomechanical assessments and the severity of keratoconus (KC) based on corneal tomographic assessments in patients with different stages of KC. Methods: Fifty-three patients who presented with clinical KC in 1 eye and KC suspect in the fellow eye were included. Corneal tomographic and biomechanical assessments were performed using the Pent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
51
2
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(60 citation statements)
references
References 39 publications
2
51
2
5
Order By: Relevance
“…It was reported that the thinning of the corneal apex is a typical character of the keratoconus eye [ 38 ]. The current results reported that SP-A1 in keratoconus eyes was statistically positively related with TCT, which was consistent with previous studies [ 16 , 21 , 32 ]. Several researchers had proposed that the thinning of the cornea in keratoconus patients would decrease the biomechanical properties, which in turn resulted in the focal weakening of cornea, and the decrease of corneal properties might further thin the cornea [ 15 , 39 , 40 ].…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…It was reported that the thinning of the corneal apex is a typical character of the keratoconus eye [ 38 ]. The current results reported that SP-A1 in keratoconus eyes was statistically positively related with TCT, which was consistent with previous studies [ 16 , 21 , 32 ]. Several researchers had proposed that the thinning of the cornea in keratoconus patients would decrease the biomechanical properties, which in turn resulted in the focal weakening of cornea, and the decrease of corneal properties might further thin the cornea [ 15 , 39 , 40 ].…”
Section: Discussionsupporting
confidence: 94%
“…Thus, a multicenter study should be conducted to explore the distribution of SP-A1 in different populations in the future. In addition, the current study found that the SP-A1 value in keratoconus eyes was lower than that in normal eyes, which was similar to other reports [ 3 , 13 , 17 , 21 ]. The differences in SP-A1 values indicated that keratoconus eyes had weaker corneal stiffness than normal eyes, which provide reference for exploring the etiology of keratoconus.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Koh et al have observed similar results for DAR2, IntInverseR and SPA1 based on anterior and posterior curvature as well as corneal thickness. Steeper corneas (anterior and posterior curvature) have been associated with higher DAR2, higher IntInverseR and lower SPA1 [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Corneal focal biomechanical weakness is considered to play a major role during the pathological changes in KC [2][3][4][5][6][7]. Corneal visualization Scheimpflug technology (Corvis ST, Oculus Optikgeräte GmbH; Wetzlar, Germany) is commonly used to assess corneal biomechanics [8].…”
Section: Introductionmentioning
confidence: 99%